PEKANBARU DALAM MENJAMIN MUTU PENDIDIKAN PADA MASA PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) TAHUN 2020 - Sarah Florita; Auradian Marta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The current state of the Corona Virus Disease (COVID-19) pandemic has greatly impacted the implementation of teaching and learning at various levels of education. All meetings that were previously held face-to-face or in person are now being turned into online activities, which are better known as learning from home (BDR) or online learning. However, in its implementation, online learning or learning from home itself has many shortcomings, which are found from various parties, both from teachers or teaching teams, students, parents or guardians of students, as well as the network and applications used. The purpose of this study is to find out how the City Government's strategy is to ensure the quality of education in the midst of the 2020 COVID-19 pandemic. In this research, the approach used is a qualitative approach and this type of research is carried out descriptively. The location of this research was carried out at the Pekanbaru City Education Office, as well as interviews and documentation on data collection techniques. The results of this study are firstly, the strategies adopted by the City Government in ensuring the quality of education during the COVID-19 pandemic are described in four groups of strategies, namely aggressive strategies in the form of online learning and implementing the Independent Learning program, conservative strategies, namely offline learning, innovative strategies consisting of home visits and using YouTube as a medium for delivering material, and preventive strategies, namely by evaluating every month. Second, the inhibiting factors in carrying out the Pekanbaru City Government's strategy in ensuring the quality of education during the COVID-19 pandemic consisted of internal factors, namely obstacles in carrying out circulars, the absence of special programs during the pandemic, budget constraints, and lack of training and encouragement. And the external factor is the economic condition of the community, constrained by the network, the lack of parental participation, and the decline in learning interest and student concentration. Key Word: Government Strategy, Quality of Education, COVID-19 Pandemic